Analysis of Physico-Chemical Parameters of Water of Ponds/Lakes in and Around Arsikere Taluk, Hassan District, Karnataka, India - Shivashankar, Poornima Bhari; Alavandi, Shwetha (Asian Journal of Biological and Life Sciences)
Arsikere is one of the historical old towns originates during the Hoysala dynasty, holds several lakes/ponds in and around its geography. Published reports on physic-chemical parameters of lakes/ponds in and around Arsikere is poor. To know about the physico-chemical properties of lakes/ponds of Arsikere, as it is necessitated because water from these lakes/ponds are drinking source to various animal species including man some extent. Hence, present investigation was undertaken by selecting three perennial ponds namely: Arsikere pond or Doddakere, Kallanaikanahalli Kere and Kellengere Kere were selected within the circumference of five kilometer radius to investigate the water quality during different seasons from February, 2022 to January, 2023. Water samples were collected using standard methods and analyzed the physicochemical parameters namely: temperature, pH, conductivity, turbidity, total suspended solids, dissolved oxygen, free carbon dioxide, Biochemical Oxygen Demand (BOD), calcium carbonate, chloride, total phosphorus, nitrogen and total hardness were measured in the laboratory. Results revealed quite interesting facts. The physical parameters such as temperature, pH, conductivity, turbidity and total suspended solids were not alike during different seasons and indicated significant difference between the ponds. Moreover, Spearman’s correlation coefficient between pH, conductivity, turbidity and total suspended solids with water temperature indicated positive correlation during most of the seasons. Similarly, chemical parameters such as dissolved oxygen, free carbon dioxide, Biochemical Oxygen Demand (BOD), calcium carbonate, chloride, total phosphorus, nitrogen and total hardness were also differed significantly during different seasons between the ponds. Further, Spearman’s correlation coefficient between dissolved oxygen, free carbon dioxide, Biochemical Oxygen Demand (BOD), calcium carbonate, chloride, total phosphorus, nitrogen and total hardness with water temperature indicated positive correlation during most of the seasons. Although, Arsikere pond or Doddakere, Kallanaikanahalli Kere and Kellengere Kere are located within the radius of five kilometers, but their topography is slightly varied and interestingly the physical and chemical parameters of these pond water were dissimilar and varied considerably. Water is one of the vital solvents, required by all living beings including man, its physico-chemical parameters as per the APHA standard norms are necessary to maintain the basic characteristics to understand the healthy status of aquatic habitat. Moreover, understanding the physico-chemical parameters of ponds/lakes imperative to maintain the health of aquatic habitats and in turn balance the biotic and abiotic components of aquatic ecosystems.
Keywords: Lakes; Physico-Chemical parameters; Ponds; Seasonal variations